EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN MENULIS TEGAK BERSAMBUNG SISWA KELAS II SDN 20 CAKRANEGARA - Nurinayah, Nurinayah; Rohana Hariana Intiana, Siti; Indraswati, Dyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the effectiveness of the discovery learning model in improving the cursive writing skills of second-grade students at SDN 20 Cakranegara. The research design used in this study is a quasi-experimental design with a nonequivalent control group. The population of this study consists of 40 second-grade students at SDN 20 Cakranegara. The data collection technique used in this study is a pretest-posttest assessment of students' cursive writing skills using performance-based tasks and the implementation of the learning process. Descriptive statistical analysis is used in this study. The results of this study indicate that the discovery learning model is effective in improving the cursive writing skills of second-grade students at SDN 20 Cakranegara, as evidenced by the N-Gain test result of 63.61 with a moderate interpretation of cursive writing skills improvement. Therefore, it can be concluded that the discovery learning model is effective in enhancing the cursive writing skills of second-grade students at SDN 20 Cakranegara.